SEDIMENTOLOGY AND PALEOENVIRONMENT OF DEPOSITION OF YOLDE FORMATION OF THE GONGOLA BASIN (UPPER BENUE TROUGH, NIGERIA): DEDUCED FROM GRAIN SIZE DISTRIBUTION - Shettima. B; Nabage. N.A; Sulaiman A; Usman.,M.B; Tabale R.P (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The Yolde Formation is composed of sandstones, siltstones, mudstones, claystones, shales and minor limestones. These lithlogic units display a wide variety of colours ranging from brown, buff variegated colours indicating deposition in an oxidizing environment. Granulometric analysis showed that the sediments are dominantly moderately sorted and are mostly positively skewed. The bivariate plots of standard deviation vs. mean, standard deviation vs. skewness, standard deviation vs. first percentile, mean vs. first percentile and C-M pattern showed a dominance of fluvial environment. However, that of mean vs. first percentile indicated a prevalence of coastal environment. The probability curve plots show a dominance of two-sand population curves, indicating a prevalence of unidirectional currents. Paleocurrent analysis has shown that the Yolde Formation has a dominant source from the north-eastern direction, but with very minor contributions from the northwest.